Mengasah Soft Skill dan Profesionalisme melalui Mini Seminar: Program Pengabdian untuk Mahasiswa Bisnis dan Komunitas Lokal - Zulfa Ahmad Kurniawan; Siti Nur Aisyah; Arif Mubarok; Miftahurrahmah (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2024)
The challenges faced by higher education institutions have intensified with the increasing popularity of artificial intelligence (AI) technology. Technological advancements have replaced certain types of jobs and influenced the labor market. Consequently, lecturers must adopt new innovations and approaches in education to develop and enhance students' soft skills. The Mini Seminar is a presentation-based learning model designed with a simple concept. The objective of this activity is to achieve course learning outcomes (CPMK) more optimally while honing students' soft skills. The implementation of the activity consists of preparation, execution, and evaluation stages. The approach used in this activity is Participatory Action Research (PAR). The results of the questionnaire indicate that the Mini Seminar improves the quality of learning and student motivation. Therefore, this activity effectively hones students' soft skills and optimally achieves course learning outcomes. Tantangan perguruan tinggi semakin besar semenjak teknologi artificial intelligence (AI) semakin popular. Kemajuan teknologi telah menggantikan beberapa jenis pekerjaan dan mempengaruhi pasar tenaga kerja. Inovasi dan pendekatan baru harus dilakukan oleh Dosen dalam melaksanakan Pendidikan agar mampu mengasah dan membentuk soft skills. Mini Seminar adalah model pembelajaran presentasi yang dikemas dengan konsep yang sederhana. Tujuan kegiatan ini adalah mewujudkan capaian pembelajaran mata kuliah (CPMK) secara lebih optimal sekaligus mengasah soft skill mahasiswa. Pelaksanaan kegiatan terdiri dari tahap persiapan, tahap pelaksanaan, dan tahap evaluasi. Pendekatan yang digunakan dalam kegiatan ini adalah Participatory Action Research (PAR). Hasil kuisioner menunjukkan mini seminar meningkatkan kualitas pembelajaran dan motivasi mahasiswa. Sehingga kegiatan ini mampu mengasah soft skill mahasiswa dan mewujudkan capaian pembelajaran mata kuliah secara optimal.